Responsibility for the legal costs in case of procedural complicity in civil and commercial proceedings - Julia V. Kaizer (Правоприменение)
The subject of the paper are basic principles for the responsibility for the legal costs in case of procedural complicity and consolidation of these principles in the procedural legislation.The purpose of the article is to confirm or disprove hypothesis that the basis of principles for imposing the responsibility for the legal costs on co-plaintiff or codefendant includes substantive criterion (the nature of the disputed material relationship) and procedural criterion (the procedural status of the co-participant).The methodological basis of the research is the dialectical method of cognition and the resulting private-scientific methods, in particular: the system-structural method and the method of comparative law.The main results and scope of their application. Civil and commercial procedural legislation does not regulate the issue of responsibility for the legal costs in case of procedural complicity. The mechanism of such a responsibility has a significant influence on the formation of legal bodies’  position in resolving the issue from whom and in what amount the costs of the of the case consideration are to be recovered in the case of several claimants or defendants participating in the dispute.The author proposed four principles to imposing the responsibility for the legal costs on the parties in civil and arbitration proceedings due to the content of the controversial material legal relationship. 1) The principle of equal share distribution of legal costs among the parties is the main principle for recovering legal costs in the case of procedural complicity. This principle is applicable in all cases arising from legal relations with a shared plurality of persons on the creditor’s or the debtor’s side. 2) The principle of joint collection of legal costs is applicable for disputes in which joint debtors or joint creditors take part. 3) The exclusion from the principle of equal imposing the responsibility for the legal costs is allowed by the court in case of a violation of procedural rights by one or several parties. 4) The inadmissibility of imposing the responsibility for the legal costs to the plaintiff in favor of improper co-defendant in the case when this co-defendant appeared on the court’s initiative.It is unreasonable to use the criterion of the actual procedural behavior of the parties during the imposition the responsibility for the legal costs, because this criterion is vague and evaluative, it depends on the will of the person who claims to reimburse legal costs and on the opinion of the judge resolving this issue. The proposed principle of legal costs equal sharing among the parties will not affect the adversarial character in the civil and arbitration procedure.Conclusions. In order to unify approaches of courts and to prevent a discretionary attitude to this issue, it is necessary to develop basic principles for imposition of responsibility for the legal costs in case of procedural complicity and consolidation of these principles in the procedural legislation. The nature of the controversial material relationship is put on the basis for the joining of the parties in the civil and commercial proceedings. This criterion should also be taken into account by the court when deciding on the court costs distribution among the parties involved in the case.